Analisis Peran Orang Tua Dalam Memotivasi Belajar Siswa Kelas V Sd Negeri 1 Kalibagor, Banyumas - Syafa Aludra Thara; Sriyanto Sriyanto (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the role of parents in motivating the learning process of fifth-grade students at SD Negeri 1 Kalibagor, Banyumas. Employing a descriptive qualitative design, data were collected through classroom and home observations, interviews with the class teacher, students, parents, neighbors, and a teacher, and documentation of grade books and student data records. Informants were selected via purposive sampling to include four students (with low and high motivation), four parents (active and less active), two neighbors, and one class teacher. Instruments consisted of observation, interview, and documentation guides, with data validity ensured through triangulation. Results indicated that parental involvement—through encouragement, supervision, and supportive learning environments—positively influenced student motivation. High motivation was observed in students with active parental support, while those lacking such support exhibited lower participation and academic achievement. Based on these findings, it is recommended that schools and educational authorities facilitate active parental engagement through coaching programs and involvement in learning activities to enhance student motivation and academic outcomes.